Proses Pembuatan Nanomaterial Elektroda Baterai Lithium Dari Pasir Besi Alami Magnetik Fe3O4 Didoping PVDF - Maulinda Maulinda; T. Muhammad Zulfikar; Saisa Saisa (Fakultas Teknik, 2022)
Lithium battery is a portable battery which has the advantages of long cycle life and high energy density. The improvement of electrode quality performance can be done by adding a binder to maintain the physical structure of the electrode, namely Fe3O4 magnetic nanoparticles whose electrical conductivity has been increased by the addition of PVDF. Then the Fe3O4 /PVDF compound doping process was carried out using the sol-gel method (10:10, 10:20 and 10:30 ratios). This study aims to determine the best comparison of the addition of PVDF as an electrode binding material capable of binding magnetic nanoparticles (Fe3O4) observed with XRF, XRD, SEM and Electrical analysis of materials using LC-Meter. The results of the best Fe3O4 magnetic chemical composition based on XRF characterization showed a very high number, namely 87.10%. The value of the electrical analysis of Fe3O4 nanoparticles with the addition of a PVDF electrode binding matrix shows the best electrical conductivity treatment results are obtained by adding a PVDF electrode binding material ratio of 10:30, the greater the addition of PVDF, the higher the capacitance and inductance values, while the smaller the resistance value. indicates that the value of the conductivity or electrical conductivity of the Fe3O4 /PVDF material is getting higher.